Peran Orang Tua, Guru dan Teman Sebaya dalam Membantu Siswa Mencapai Tugas-Tugas Perkembangan - Musri Ali Gapur (Universitas PGRI SUMATERA BARAT, 2022)
The background of this research is that there are some students whose developmental tasks have not developed well, this study aims to reveal the role of parents, teachers and peers in helping students achieve developmental tasks, the questions of this research are; 1. What is the role of parents in helping students achieve developmental tasks at MTs S 02 Al-Munawwaroh kepahiang, 2. What is the role of teachers in helping students achieve developmental tasks at MTs S 02 Al-Munawwaroh kepahiang, 3. What is the role of peers in helping students achieve developmental tasks at MTs S 02 Al-Munawwarah, the research subjects are parents, teachers and peers. The research method used in this study is a type of qualitative research. The research approach in this study is descriptive. This study does not have a hypothesis, because this research is not intended to test hypotheses that have been formulated to be rejected or accepted, but emphasizes collecting data to describe the actual situation in the field, collecting data by means of interviews and documentation. Based on the results of the study, in general, there is a role for parents, teachers and peers in helping students achieve assignments at MTs S 02 Al-Munawwarah kepahiang. In particular, there is a role for parents in helping students achieve developmental tasks at MTs S Al-Munawwaro Kepahiang. There is a teacher's role in helping students achieve developmental tasks at Mts S 02 Al-Munawwaro Kepahiang. There is a role of peers in helping other students in achieving developmental tasks at MTs S 02 Al-Munawwaroh kepahiang.